Determinants of Inflation Expectations in the Euro Area - Richhild Moessner (Intereconomics)
Abstract Euro area inflation has been rising strongly in the wake of the COVID-19 pandemic, giving rise to concerns that there could be second-round effects, with higher inflation leading to higher inflation expectations, which in turn lead to higher inflation. This could result in more persistent rises in inflation.